Analysis of Students' Critical Thinking Skills Through the Pakem Learning Model in Science Subject Class VI SD Negeri 78 Palembang - Lestari, Wahyu; Hakim, Lukman; Nindiati, Dina Sri (Jurnal Pendidikan Amartha, 2024)
Critical thinking ability is a high-level thinking ability that aims to make reasonable decisions to help the problem solving process actively and skillfully in analyzing, applying and evaluating information obtained or resulting from observations of elementary school students. The learning model is one of the important things in creating an active, creative, effective and enjoyable learning process. The PAKEM model is an appropriate model to use in the learning process. This research aims to determine the critical thinking abilities of class VI students using the PAKEM model in science learning at SD Negeri 78 Palembang. This research uses an experimental method with a quantitative approach. The subjects in this research are 25 VIC class elementary school students. Data collection techniques in this research use observation, tests, interviews and documentation. Data analysis techniques use the normality test, homogeneity test and T-Test. The results of this research found that there were 8 students with high critical thinking skills, with a score range of 85-100, getting a percentage of 32%. Medium critical thinking ability, totaling 12 students, with a score range of 75-80, got a percentage of 48% and low critical thinking ability, totaling 5 students, with a score range of 65-70, got a percentage of 20%. The results of the critical thinking skills of class VIC students using the PAKEM model in science learning at SD Negeri 78 Palembang overall students reached 82.4% in the good category.